MBECS: Microbiome Batch Effects Correction Suite - Michael Olbrich; Axel Künstner; Hauke Busch (BMC Bioinformatics, 2023)
Abstract Despite the availability of batch effect correcting algorithms (BECA), no comprehensive tool that combines batch correction and evaluation of the results exists for microbiome datasets. This work outlines the Microbiome Batch Effects Correction Suite development that integrates several BECAs and evaluation metrics into a software package for the statistical computation framework R.